Politeness As a Strategy of Attack in Presidential Debate in Indonesia 2019 - Rossy Halimatun Rosyidah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
This research was conducted to know what are the politeness as strategy of attack in the presidential debate in Indonesia 2019 and what is the dominant of politeness strategy used by the candidates. The method of this research is descriptive qualitative. The research subject is the dialogue of Presidential and Vice-presidential candidates. The research object is the politeness strategy. The instrument is the researcher herself and the indicator table, the data collection is from YouTube, and the data analysis uses Brown and Levinson’s theory. The validity is triangulation method. The result of this research is the presidential candidate number 1 used all kinds of politeness strategies. Therefore, the dominant used theory bald of record. Then the vice-presidential candidate just used positive politeness. Besides, the candidate number 2 used bald of record and off records strategy. Therefore, the dominant used theory bald of record. Then the candidate of the vice president just used bald of records. Bald of record is applied to criticizing, expressing hatred, getting angry, commanding, warning, resisting, and paying attention.